Promoting species protection with predictive modelling: Effects of habitat, predators and climate on the occurrence of the Siberian flying squirrel. (February 2019) - Jokinen, Maarit; Hanski, Ilpo; Numminen, Elina; Valkama, Jari; Selonen, Vesa
Abstract: Species distribution models (SDMs) can be used to predict species occurrence and to seek insight into the factors behind observed spatial patterns in occurrence, and thus can be a valuable tool in species conservation. In this study, we used MaxEnt software to explain the occurrence of a protected forest-dwelling species, the Siberian flying squirrel. We produce occurrence maps covering the main distribution area for the species in the European Union. Using an exceptionally extensive presence-absence dataset collected with a standardized method, we evaluated the relative role of predation pressure, climate, and amount of habitat affecting flying squirrel occurrence. We found that regional variation in mean winter temperature had relatively large predictive power for flying squirrel occurrence. In addition, the regional abundance of flying squirrels was partly explained by differences in predation pressure. The results also support the conclusion that areas with older forests and nearby agricultural areas are optimal for the species. Our study shows that multiple factors affect the species' occurrence in large spatial scales. We also conclude that climate is having a large effect on species occurrence, and thus the changing climate has to be taken into account in conservation planning. Our results help conservation managers in targeting surveys and protection measures on various spatial scales, and decision makers in focusing on the factors that drive the species' occurrence. Our results also indicate that we would need additional tools and measures in the EU for achieving a favourable conservation status of those species that occur in commercial forests.